Professionalization of artists. Creation of the Escuela de Arte Escénico at Universidad Nacional, Heredia, Costa Rica (1973-1985) - Rojas Mejías, Diana (Revista de historia., 2021)
This article refers to the history of Escuela de Arte Escénico of the Universidad Nacional from 1973 to 1985. During this period, there was an interest to professionalize this discipline in a public university with limited human and economic resources; besides in 1970s’ Costa Rica, had a student population and a Heredia audience to attract. To approach this topic, this article focus the way this career was created as Universidad Necesaria conception and in a country where there were already institutions dedicated to this teaching. Also, it explains the operational infrastructure condition and plan career. Finally, the artistic and labor careers of the earliest teachers are emphasized in the research in order to understand the political orientation of the school at certain occasions; as well as the names of Teatro Estudio y Arte Escénico which this unit was distinguished from other careers and occupational demands.